2009
DOI: 10.1177/1934578x0900401114
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Functional Diversity of Natural Products from Plant Associated Endophytic Fungi

Abstract: This review describes examples of naturally occurring bioactive compounds obtained from fungal endophytes from various host plants. The main topics addressed are sources, identification, biological activity, biosynthesis, and ecological and chemosystematic significance of those bioactive compounds whose sources were well defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
97
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 126 publications
(145 reference statements)
4
97
0
4
Order By: Relevance
“…However, biology and ecology of most endophytes are not known but are assumed to vary according to host and environment [7,8,38]. A huge number of authors suggested that endophytes are good sources of novel secondary metabolites that possess antibacterial [37,65] antifungal [15,65] and anticancer properties [36]. In this study, the endophytic mycobiota of the medicinal plant Tinospora cordifolia Miers., was studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, biology and ecology of most endophytes are not known but are assumed to vary according to host and environment [7,8,38]. A huge number of authors suggested that endophytes are good sources of novel secondary metabolites that possess antibacterial [37,65] antifungal [15,65] and anticancer properties [36]. In this study, the endophytic mycobiota of the medicinal plant Tinospora cordifolia Miers., was studied.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesised that if interactions between fungi occur within leaves, these may in turn have effects on insect feeding. Given that these interactions result in the production of a variety of metabolites (Verma et al 2009), we further hypothesised that generalist and specialist insects may respond in a different manner, depending on their reactions to secondary metabolites (Schoonhoven et al 2005). All previous studies of herbaceous endophytes and insects have used single species of fungi, yet in nature an insect may ingest leaf material that contains one, two or more species of endophyte, plus the chemicals that these fungi produce or induce.…”
Section: Introductionmentioning
confidence: 99%
“…Endophytes are microorganisms that reside symbiotically to borderline pathogenically in virtually every plant without causing any externally apparent signs or symptoms of their presence [14,23,26]. In exchange for the host providing an appropriate environment for the endophyte, the fungal endophyte will produce volatile organic compounds (VOCs) that ward off pathogenic microorganisms [14,17,18,23,26].…”
Section: Introductionmentioning
confidence: 99%
“…In exchange for the host providing an appropriate environment for the endophyte, the fungal endophyte will produce volatile organic compounds (VOCs) that ward off pathogenic microorganisms [14,17,18,23,26]. Because of the production of VOCs, endophytes allow their host plants to withstand attacks by pathogens as well as harsh environments, including drought and salinity [23].…”
Section: Introductionmentioning
confidence: 99%